Placental Growth Factor for the Prediction of Adverse Feto-Maternal Outcome in Patients with Pre-Eclampsia (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Placental Growth Factor (PlGF) level is reported to be low in preeclampsia. Recent research suggested that it can be a promising tool for predicting adverse fetomaternal outcomes compared to nonspecific biomarkers. This study evaluated the predictive accuracy of maternal serum PlGF level for adverse fetomaternal outcomes in pre-eclamptic women.   Materials and methods: Seventy women with preeclampsia from the Department of Obstetrics and Gynecology of Chittagong Medical College Hospital from January 2021 to December 2021. PIGF level at admission  was measured by ELISA method, and value >100 and  £100 pg/ml was defined as normal and low, respectively. Patients were prospectively followed till delivery to observe fetomaternal outcomes.   Results: Out of 70 women, 28 (40%) developed adverse fetomaternal outcomes. The median level of PlGF was significantly lower among women with adverse fetomaternal outcomes than their counterparts [37.0 (18.9 - 61.5) pg/ml versus 122.7 (91.3-156.3) pg/ml, p